Analysis of the anti-cancer effects of cincau extract (Premna oblongifolia merr) and other types of non- digestible fibre using faecal fermentation supernatants and Caco-2 cells as a model of the human colon - Nurdin, S.; Le Leu, R.; Young, G.; Stangoulis, J.; Christophersen, Claus; Abbott, C. (MDPI Publishing, 2017)
© 2017 by the authors. Green cincau (Premna oblongifolia Merr) is an Indonesian food plant with a high dietary fibre content. Research has shown that dietary fibre mixtures may be more beneficial for colorectal cancer prevention than a single dietary fibre type. The aim of this study was to investigate the effects of green cincau extract on short chain fatty acid (SCFA) production in anaerobic batch cultures inoculated with human faecal slurries and to compare these to results obtained using different dietary fibre types (pectin, inulin, and cellulose), singly and in combination. Furthermore, fermentation supernatants (FSs) were evaluated in Caco-2 cells for their effect on cell viability, differentiation, and apoptosis. Cincau increased total SCFA concentration by increasing acetate and propionate, but not butyrate concentration. FSs from all dietary fibre sources, including cincau, reduced Caco-2 cell viability. However, the effects of all FSs on cell viability, cell differentiation, and apoptosis were not simply explainable by their butyrate content. In conclusion, products of fermentation of cincau extracts induced cell death, but further work is required to understand the mechanism of action. This study demonstrates for the first time that this Indonesian traditional source of dietary fibre may be protective against colorectal cancer.